1998
DOI: 10.1007/s001150050360
|View full text |Cite
|
Sign up to set email alerts
|

„Paradoxe” Herniation nach Entlastungstrepanation

Abstract: The intracranial space is divided into two large compartments by the tentorium. The hydrostatic pressure of spinal fluid is responsible for buoyancy of the brain within these compartments. In patients with craniectomy this equilibrium is exposed to atmospheric pressure. We report on four cases of reversible herniation after either bilateral or unilateral decompressive craniectomy performed for increased intracranial pressure (ICP) and failure of conservative ICP treatment. All four patients had survived a seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 15 publications
0
17
0
3
Order By: Relevance
“…Patients with paradoxical herniation should be treated with intravenous fluids, Trendelenburg positioning, and clamping of CSF drainage; hyperosmolar therapy should be discontinued, and early attention given to insertion of a blood patch. 61,76,93 Cranioplasty may act to reduce the negative pressure gradient and should also be considered in the management of paradoxical herniation.…”
Section: Postoperative Complications Within 30 Daysmentioning
confidence: 99%
“…Patients with paradoxical herniation should be treated with intravenous fluids, Trendelenburg positioning, and clamping of CSF drainage; hyperosmolar therapy should be discontinued, and early attention given to insertion of a blood patch. 61,76,93 Cranioplasty may act to reduce the negative pressure gradient and should also be considered in the management of paradoxical herniation.…”
Section: Postoperative Complications Within 30 Daysmentioning
confidence: 99%
“…5 Subsequently, 13 more patients with paradoxical herniation provoked by lumbar puncture were described in a series of 4 cases, whose authors first used the term "paradoxical herniation," 16 and in 9 single case reports. 2,[8][9][10][11]14,17,19,20 Cases of paradoxical herniation provoked by lumbar puncture are summarized in Table 1.…”
mentioning
confidence: 99%
“…Since Yamamura et al 15) reported in 1977, the syndrome of the sinking skin flap with neurological deterioration has been reported in the literature 2,5,7,8,11,12) . Many investigators have sought to explain the pathophysiology of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…According to this theory, George et al 3) showed that there was a correlation between the restoration of the midline shift and the clinical improvement following cranioplasty in a series of angiographies. Recently, several authors 8,12) proposed that a negative gradient between atmospheric-and intracranial pressure, which is aggravated by changes in the CSF compartment following CSF hypovolemia to be the mechanism of neurological deterioration after craniectomy.…”
Section: Discussionmentioning
confidence: 99%